Typical Spike-and-Wave Activity in Hypoxic-Ischemic Brain Injury and its Implications for Classifying Nonconvulsive Status Epilepticus - Mader, Edward C. (Libertas Academica, 2012)
INTRODUCTION: Typical spike-and-wave activity (TSWA) in the electroencephalogram (EEG) indicates idiopathic generalized epilepsy (IGE). IGE-related nonconvulsive status epilepticus (NCSE) is typically an absence status epilepticus (ASE). ASE and TSWA respond dramatically to benzodiazepines. Patients with no history of seizure/epilepsy may develop ASE “de novo” in the context of an acute brain disorder. However, we are aware of only one previous case of de novo ASE with TSWA in hypoxic-ischemic brain injury. CASE PRESENTATION: A 65-year-old man, with congestive heart failure and history of substance abuse, survived cardiorespiratory arrest after 18 minutes of cardiopulmonary resuscitation. Post-resuscitation, the patient was in coma with intact brainstem function. Toxicology was positive for cocaine and marijuana. Eyelid myoclonus suggested NCSE, which was initially treated with lorazepam and fosphenytoin. EEG monitoring showed sustained TSWA confirming NCSE and demonstrating de novo ASE (the patient and his family never had seizure/epilepsy). The TSWA was resistant to lorazepam, levetiracetam, and low-dose midazolam; it was eliminated only with midazolam at a dose that resulted in burst-suppression (≥1.2 mg/kg/hour). CONCLUSION: This is an unusual case of TSWA and hypoxic-ischemic brain injury in a patient with no history of seizure/epilepsy. The TSWA was relatively resistant to benzodiazepines suggesting that cerebral hypoxia-ischemia spared the thalamocortical apparatus generating TSWA but impaired the cortical/thalamic inhibitory circuits where benzodiazepines act to suppress TSWA. Albeit rare, ‘post-hypoxic’ TSWA offers us some valuable insights for classifying and managing nonconvulsive status epilepticus.